2019
DOI: 10.1002/pon.5168
|View full text |Cite|
|
Sign up to set email alerts
|

Examining the feasibility, acceptability, and potential utility of mobile distress screening in adult cancer patients

Abstract: Objective: A common method of distress monitoring in cancer patients relies on static and retrospective data collected in-person at the time of a health care provider appointment. Relatively little work has examined the potential usefulness of mobile distress monitoring using cancer patients' smartphones. The current study deployed longitudinal distress monitoring using secure text messaging.Methods: In an observational study, a total of 52 cancer patients receiving active cancer treatment (M age = 58, 62% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Cancer Care Ontario’s systematic ESAS distress screening commenced in 2007, with rates increasing steadily from approximately 20% in 2009 to 59% in 2015, but remaining below the provincial target of 70% screened (range 31% at lowest performing to 91% at highest performing centers). Chow et al [ 25 ] also found that patients completed a brief distress screener 75% of the time they received a text message, suggesting feasibility of remote ePRO screening, as per our PROMPT-Care model.…”
Section: Discussionmentioning
confidence: 78%
“…Cancer Care Ontario’s systematic ESAS distress screening commenced in 2007, with rates increasing steadily from approximately 20% in 2009 to 59% in 2015, but remaining below the provincial target of 70% screened (range 31% at lowest performing to 91% at highest performing centers). Chow et al [ 25 ] also found that patients completed a brief distress screener 75% of the time they received a text message, suggesting feasibility of remote ePRO screening, as per our PROMPT-Care model.…”
Section: Discussionmentioning
confidence: 78%
“…The electronic database search identified a total of 4449 studies, out of which 18 studies involving 5821 patients were included in the final qualitative synthesis ( Figure 1 ). Of the included studies, 9 (50%) were randomized trials [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and 9 (50%) were non-randomized interventional/observational studies [ 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] ( Table 1 , Table S3 ). Sixteen of 18 studies (89%) were conducted in high-income countries (HICs) [ 11 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 ], the majority ( n = 11) in the United States [ 11 , 26 , 28 , 29 , 33 , 34 , 35 , 36 , 38 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 9 (50%) were randomized trials [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] and 9 (50%) were non-randomized interventional/observational studies [ 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] ( Table 1 , Table S3 ). Sixteen of 18 studies (89%) were conducted in high-income countries (HICs) [ 11 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 ], the majority ( n = 11) in the United States [ 11 , 26 , 28 , 29 , 33 , 34 , 35 , 36 , 38 , 40 , 41 ]. Two studies (11%) were conducted in low- and middle-income countries (LMICs), both in Brazil [ 30 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolva and colleagues determined that use of an online risk algorithm to assess suicidality in cancer patients was ethically sound and feasible . Text messaging has also been shown to be a feasible and acceptable approach for real‐world distress screening in adult cancer patients …”
mentioning
confidence: 99%